Reliability, maintainability, and supportability : best practices for systems engineers - Tortorella, Michael, 1947- (John Wiley & Sons, Inc., 2015)
"Provides exercises in each chapter, allowing the reader to try out some of the ideas and procedures presented in the chapter"--